The psychology of humor : an integrative approach - Martin, Rod A.; Ford, Thomas E. (Academic Press, an imprint of Elsevier, 2018)
Most of us laugh at something funny multiple times during a typical day. Humor serves multiple purposes, and although there is a sizable and expanding research literature on the subject, the research is spread in a variety of disciplines. The Psychology of Humor, 2e reviews the literature, integrating research from across subdisciplines in psychology, as well as related fields such as anthropology, biology, computer science, linguistics, sociology, and more. This book begins by defining humor and presenting theories of humor. Later chapters cover cognitive processes involved in humor and the effects of humor on cognition. Individual differences in personality and humor are identified as well as the physiology of humor, the social functions of humor, and how humor develops and changes over the lifespan. This book concludes noting the association of humor with physical and mental health, and outlines applications of humor use in psychotherapy, education, and the workplace. In addition to being fully updated with recent research, the second edition includes a variety of new materials. More graphs, tables, and figures now illustrate concepts, processes, and theories. It provides new brief interviews with prominent humor scholars via text boxes. The end of each chapter now includes a list of key concepts, critical thinking questions, and a list of resources for further reading.